Exploring Research Trends and Mechanisms: Maternal Diabetes and Neural Tube Defects (1991–2023) - Cao L; Xi Y; Jing Z; Bao Z; Bai B; Lian X; Zhang X; Di J; Liu F (Journal of Multidisciplinary Healthcare)
Lijun Cao,1,* Yujia Xi,2,3,* Zhinan Jing,3,* Zhuocheng Bao,3 Bo Bai,1 Xia Lian,1 Xiuping Zhang,1 Jingkai Di,4 Fan Liu1 1Department of Neurology, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 2Department of Urology, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 3Male Reproductive Health Research Center, Shanxi Medical University, Jinzhong, Shanxi, People’s Republic of China; 4Department of Orthopedics, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingkai Di; Fan Liu, Second Hospital of Shanxi Medical University, 382 Wuyi Road, Taiyuan, Shanxi, 030001, People’s Republic of China, Email jingkaidi2000@163.com; liufanykx0701@163.comBackground: Neural tube defect (NTD) is the second most common congenital neuropathy in the world. Maternal diabetes is an important factor leading to the occurrence of NTD in offspring. However, existing studies lack a systematic analysis of the correlation between maternal diabetes and NTDs, as well as an exploration of NTD pathogenesis and associated preventive strategies. Consequently, there is a need for a thorough examination of the literature pertaining to NTDs and maternal diabetes to elucidate a comprehensive understanding, identify research focal points, and anticipate future developmental trends.Methods: The literature related to NTDs and maternal diabetes from 1991 to 2023 was retrieved from the Web of Science Core Collection (WoSCC). Bibliometric software CiteSpace (version 6.2.6) was used for co-occurrence/citation network analysis and to draw a knowledge visualization map.Results: A total of 382 articles and reviews were included in the final analysis. Findings revealed an increasing trend in annual publication rates. The University of Maryland Baltimore emerged as the institution with the highest number of publications, while the American Journal of Obstetrics and Gynecology and Birth Defects Research Part A-Clinical and Molecular Teratology stood out as the most prolific research journals. EA Reece was identified as the leading contributor in this domain. The United States emerged as the global leader in this field, making the most significant contribution to research endeavors. The cluster analysis of keywords obtained eight clusters, and the research focus was on the pathogenesis of NTDs induced by maternal diabetes.Conclusion: This study employed bibliometric methods to visualize the research landscape of NTDs induced by maternal diabetes, aiming to comprehend trends and identify key areas of interest in this domain. By studying the relevant mechanisms, we will search for new key targets. Meanwhile, future research needs to further explore new treatment strategies.Keywords: bibliometric analysis, neural tube defects, diabetes, research hotspots, cluster analyses, visualization, CiteSpace, VOSviewer